2008
DOI: 10.1089/aid.2008.0087
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of HIV Type 1 Drug Resistance Mutations in Algeria

Abstract: This study demonstrates for the first time HIV-1 resistance mutations to all classes of antiretroviral drugs available in Algeria (NRTIs, NNRTIs, PIs) in treated patients at failure. Moreover, it is shown that mutations to NRTIs and PIs can be observed in untreated patients in this country where there is high HIV-1 diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In this study, we observed a prevalence of 31% of HIV-1 resistance-associated mutations, 15% considering the list established by Bennett et al 12 : this was a huge increase compared to the previous analysis. 6 Nevertheless, this result is not surprising and has already been observed elsewhere. [9][10][11] In Africa, the prevalence of drug resistance mutations varies across countries, reaching 54.9% in Central Africa.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this study, we observed a prevalence of 31% of HIV-1 resistance-associated mutations, 15% considering the list established by Bennett et al 12 : this was a huge increase compared to the previous analysis. 6 Nevertheless, this result is not surprising and has already been observed elsewhere. [9][10][11] In Africa, the prevalence of drug resistance mutations varies across countries, reaching 54.9% in Central Africa.…”
Section: Discussionsupporting
confidence: 74%
“…In previous studies published in 2006 and 2008, we observed high HIV-1 diversity in Algeria with a predominance of the B subtype followed by CRF02_AG and CRF06_cpx. 5,6 In the current study, the diversity was maintained, but CRF06_cpx became widely predominant. The evolution of the HIV infection, previously originating primarily in Europe and now from others neighboring countries, surely explains this epidemiological change.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Drug resistance mutations to NRTIs and PIs have been reported in untreated patients in Algeria [21]. Moreover, HIVDR to NRTIs, NNRTIs, and PIs were described in Morocco among ART-naive patients [22].…”
Section: Introductionmentioning
confidence: 99%